2021
DOI: 10.7759/cureus.19822
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cilnidipine (L/N-type Calcium Channel Blocker) in Treatment of Hypertension: A Meta-Analysis of Randomized and Non-randomized Controlled Trials

Abstract: Introduction: Hypertension is one of the most common cardiovascular diseases, and the prevalence of hypertension continues to rise across the globe. National and international guidelines recommend angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs), calcium channel blockers (CCBs), diuretics, and beta-blockers for the management of hypertension. CCBs are among the most used antihypertensive medications and Cilnidipine is a newer dihydropyridine CCB shown to have a prolonged a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…It is postulated that Cilnidipine exhibits a high protein binding of 98% along with a high volume of distribution, which prolongs the duration of action of the molecule. A 2021 metaanalysis presented by Chakraborty R et al 7 concluded that Cilnidipine significantly reduced systolic blood pressure, diastolic blood pressure, and pulse rate in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is postulated that Cilnidipine exhibits a high protein binding of 98% along with a high volume of distribution, which prolongs the duration of action of the molecule. A 2021 metaanalysis presented by Chakraborty R et al 7 concluded that Cilnidipine significantly reduced systolic blood pressure, diastolic blood pressure, and pulse rate in hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis concludes Cilnidipine to be the firstline CCB for the management of hypertension either as a monotherapy or as a combination therapy. 7 Cilnidipine is approved for use in Japan under the brand name, Atelec ® by Ajinomoto Pharmaceuticals.…”
Section: Introductionmentioning
confidence: 99%